Pedagogy and university teacher education today in Latin America, an epistemological perspective (2021)
ABSTRACT  The analysis that is made in the present study, from the pedagogy, shows an interesting orientation, whose horizon is varnished with the epistemological vision that is imprinted on it at the current juncture. The main objective of the present investigation is analysis, from the epistemological perspective, pedagogy and university education in the Latin American context. The methodological itinerary used was hermeneutics, which according to its nature of the account of the necessary search for elements and theories, which treat and expose the subject, which served as bases for the subsequent analysis, critically, about nature of this vital issue for society and the university. This methodological orientation yielded the following results: university teacher training is seen as a heuristic form, the function of which is to teach the different programmatic contents; there is no clear epistemological vision in university training processes. This by its nature, the advancement of pedagogy and the training of university teachers, an epistemological exercise that weaves together, the teaching task and the production of knowledge.